Quando as ruas abrigam a arte: a cena hip hop no Recife (1980-2014) - Cristiano Nunes Alves (Confins)
As a way of operationalizing the notion of scene, a concept that is dear to the study of artistic production in places, we analyze the depth of the hip hop culture in Recife, from the 1980s up to the present day. This work develops an approach based upon everyday life as a geographical dimension, analyzing the connections between hip hop culture, subjects' actions within places and the sheltering of communication in the metropolis. The break down of the Hip Hop scene in Recife required not only bibliographical and documentary research on the subject, but also extensive field work, thus yielding important primary information. A timeline for hip hop in the Recife region is suggested, emphasizing two structural moments for this street culture: initially disseminated by black music parties and break dancing – hip hop's body language –, the establishment of this movement culminated in the current situation around the mid-1990s, since when rap music has been dominating the Hip Hop Scene in the Recife region. Break dancing gatherings serve as an opportunity for individuals to meet and articulate. They are geographical events of strong spatial impact and point towards the occupation of the streets and other public spaces in downtown Recife by peripheral subjects. These gatherings greatly influenced the dynamics of the first days of Recife's hip hop, prevailing roughly throughout the 1990s. The contemporary scene, stirred up by rap, indicates that the Recife region, especially its suburbs, serves as home to about 70 groups, plus two small recording labels and seven phonographic studios specialized in the production of street culture music. Today, by means of the Rap Scene, this region articulates itself with a number of places in the Brazilian urban network. One can notice that, through the actions of a group of subjects, mostly peripheral individuals, hip hop has become a constitutive element of the city. It is more a question of practices aimed at artistic satisfaction and vindication of essential citizen rights than at economic gains.